2003
DOI: 10.1007/s00431-003-1156-4
|View full text |Cite
|
Sign up to set email alerts
|

Platelet aggregation, blood viscosity and serum lipids in hypertensive and obese children

Abstract: in obese children an increased platelet aggregation and oxidative insult contribute to the development of hypertension and to the promotion of vascular damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 26 publications
3
18
1
1
Order By: Relevance
“…20 In addition, previous studies have reported that hypertension is associated with an increase in platelet reactivity. 21,22 However, it is unlikely that diminished platelet reactivity in the potassium-supplemented group was mediated through blood pressure because potassium supplementation for 3 days had no significant effect on blood pressure.…”
Section: Kimura Et Al Potassium and Platelet Reactivity 971mentioning
confidence: 99%
“…20 In addition, previous studies have reported that hypertension is associated with an increase in platelet reactivity. 21,22 However, it is unlikely that diminished platelet reactivity in the potassium-supplemented group was mediated through blood pressure because potassium supplementation for 3 days had no significant effect on blood pressure.…”
Section: Kimura Et Al Potassium and Platelet Reactivity 971mentioning
confidence: 99%
“…They showed elevated plasma viscosity, higher whole blood viscosity at both low and high shear rates and prolonged erythrocyte filtration time in obese Italian children and adolescents [4] and elevated plasma viscosity and erythrocyte aggregation in Spanish children with familiar hypercholesterolaemia [9]. Hypertensive obese children from Hungary had an elevated plasma viscosity, blood viscosity and platelet aggregation [13]. A relation between plasma viscosity, fibrinogen and the prevalence of hypertension in diabetic Turkish children [5] and improvements of the haemorheological profile upon dietary intervention in obese Italian adolescents [11] have also been documented.…”
Section: Introductionmentioning
confidence: 99%
“…In overweight children, irrespectively of hypertension, a non-significant decrease in plasma NO x was observed. In a previous study from our group a marked decrease was seen in plasma NO x in non-obese and also in obese hypertensive patients [44]. These data suggest that endothelial dysfunction, characterized by decreased plasma NO x may be a more important mechanism in EH of lean patients than in OH, but the presence of endothelial dysfunction is detectable in obesity and OH.…”
Section: Question 2 Does No Production Which Is Characterized By Plsupporting
confidence: 67%
“…Increased in vitro platelet aggregation and thromboxane B 2 (stable degradation product of TxA 2 ) levels were observed in hypertensive children [43]. In a second study, the increased platelet aggregability was also confirmed in non-obese and obese hypertensive children, and simultaneously, decreased NO and depletion of plasma free thiols, -as the sign of oxidant injury -were demonstrated in both groups of hypertensives [44]. Increase in platelet aggregation releases …”
Section: Endothelial Dysfunctionmentioning
confidence: 99%